Non-alcoholic Fatty Liver Disease and Depression: Evidence for Genotype × Environment Interaction in Mexican Americans - Manusov, Eron Grant; Diego, Vincent P.; Sheikh, Khalid; Laston, Sandra; Blangero, John; Williams-Blangero, Sarah (Frontiers in Psychiatry, 2022)
This study examines the impact of GxE interaction effects on nonalcoholic fatty liver disease (NAFLD) among Mexican Americans in the Rio Grande Valley (RGV) of South Texas. We examined potential G x E interaction using variance components models and likelihood-based statistical inference in the phenotypic expression of NAFLD, including hepatic steatosis and hepatic fibrosis (identified using vibration controlled transient elastography and controlled attenuation parameter measured by the FibroScan Device). We screened for depression using the Beck Depression Inventory-II (BDI- II). We identified significant G x E interactions for hepatic fibrosis x BDI-II. These findings provide evidence that genetic factors interact with depression to influence the expression of hepatic fibrosis.